Analysis and forecasting of energy consumption in Hebei Province, China. Issue 4 (February 2019) - Gao, Jingyao; Zhao, Huiru
Abstract: Energy plays a crucial role in the economic growth of a country or region. Therefore, scientifically predicting energy consumption and formulating a reasonable energy development strategy are important steps in promoting economic development. Based on the analysis of the economic development situation and energy consumption in Hebei Province, China, this paper uses unit GDP (Gross Domestic Product) energy consumption forecasting method, trend fitting method, and regression analysis method to predict the energy consumption in Hebei Province from 2018 to 2022, and analyses the advantages and disadvantages of the three methods of prediction to provide theoretical support for the development of Hebei's energy development policy.